North and south united to conquer viral diarrheas using innovative passive immunity strategies - Saif, Linda J. (2009)
My fortuitous journey to Argentina began 22 years ago in 1987 when I was invited by Dr Alejandro Schudel, then Director of Virology at INTA, Castelar, to visit Argentina to initiate a joint collaboration. The topic was «Rotavirus infections in calves: development and evaluation of maternal vaccines for passive immunity in calves». Passive immunity and enteric viral infections in swine and cattle were two of my major research interests at the Food Animal Health Research Program, Ohio Agricultural Research and Development Center (OARDC), The Ohio State University (OSU) in the USA. At the time, calf diarrhea was a critical problem in both beef and dairy calves, but the major causes were undefined. Our goals were first to identify the dominant pathogens in the field associated with calf diarrhea and deaths and second to develop methods for their prevention and control. To accomplish these goals, we addressed each of the following key questions in collaborative studies conducted in Argentina (INTA) and the USA (OARDC/The Ohio State University).